RISK OF ACCIDENTS AT WORK: PERCEPTIONS OF NURSING WORKERS OF A UNIVERSITY HOSPITAL - NATAL / RN - BRAZIL (Fiep Bulletin - online, 2013)
The risks to which the nursing professionals are exposed is causing many consequences, among them, diseases of work, stress, absenteeism, inappropriate posture, demotivation, among others. Objectives: This study seeks to identify the risks of an accident at work among nursing professionals from the University Hospital Onofre Lopes / RN and evaluate certain characteristics of the occurrence of such accidents. Methodology: The research was descriptive in nature to quantitative approach. The study was performed with a sample of 30 nursing professionals: 10 nurses (4.8%), 10 technicians (3.5%) and 10 assistants (14%). Data were collected in the period from September to December 2006 through a questionnaire composed of questions open and closed. Results: The analysis showed that the occurrence of accidents was higher by drillcutting (48.8%) followed by aspersion on skin and mucous with biological materials (44.2%), it was found that all accidents occurred in the unit Working at the handling of such material, and a hand reached over the place (89%) Most female sex (100%) are aged from 24 to 29 years. Higher accident incidence among nursing auxiliaries. The vast majority knows the CIPA and knows that the accident should be referred to the committee. Conclusion: These data reinforce the assertion of the accident at work is a serious problem for the nursing team and deserves further research in order to build awareness of the nursing team about the problem.
Keywords: occupational risks; work accident; nursing employees.